Comparative growth and physiological responses of two wheat (Triticum aestivum L.) cultivars differing in salt tolerance to salinity and cyclic drought stress. Issue 6 (2nd June 2016) - Abbas, Zahid Khorshid; Mobin, Mohammad
Abstract: Two cultivars of wheat ( Triticum aestivum L.) with differential salinity tolerance were compared by evaluating the growth attributes, pigment composition and accumulation of Na +, K +, Zn 2+, Fe 2+, Mn 2+ and proline. Wheat cultivars Al-Moiaya (AM) (salt tolerant) and Habbe-Druma (HD) (salt sensitive) were subjected to four levels of salinity (1.21 dS m −1, 4.4 dS m −1, 8.8 dS m −1 and 13.2 dS m −1 ) in factorial combinations with three drought stress (FC 30%, FC 60% and FC 90%) treatments in a randomized complete block design. Plant dry weight, leaf area ratio (LAR), soluble protein and total chlorophyll (Chl) content were higher in AM than HD. Salt-tolerant AM maintains a higher K + / Na + ratio and thereby is able to grow better than the salt-sensitive HD under both the stresses. The lower foliar Na + in AM resulted in retention of higher Chl content, reflected in the strong positive correlations between plant ion status and Chl contents (Na + -Chl r 2 = 0.83; Chl- Fe 2+ r 2 = 0.76; Zn 2+ r 2 = 0.93 and Mn 2+ r 2 = 0.88). In conclusion, our results suggested that the K + /Na + ratio, exclusion of Na + and ion homeostasis play much more important roles in the tolerance to salinity and drought stress than the compatible osmolyte, proline.